Urban sanitation and the decline of mortality - Harris, Bernard; Helgertz, Jonas (History of the Family, 2019)
This paper introduces a special issue of The History of the Family on sanitation and urban mortality. The special issue contains papers which focus on the impact of sanitary reforms on mortality change in Australia, Switzerland, Finland, Sweden, and England and Wales. The current paper outlines the main features of the debate over the causes of mortality change and the role played by sanitary reforms in this. It then highlights some of the methodological and other challenges posed by the definition of ‘urban’ areas, the identification of relevant sanitary reforms, and the choice of dependent variables. The paper then proceeds to summarise the main features of the individual papers before drawing some conclusions for future research.
Keywords: mortality; public health; Sanitation